SOSIALISASI PEREMPUAN SEBAGAI AGEN PEDULI LINGKUNGAN KEPADA GOW SEMARANG - Untari, Rustina; Wardhani, Dhiyan Khrisna; Harumi, Mellia; Aprilia, Kezia Yemima (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2020)
One of the parties who have great potential in environmental preservation efforts are women. Globally women provide a life for their families and at the same time manage the environment. However, due to gender power relations, their knowledge is often ignored, and they are not counted as agents of change. The Center for Women's Studies at Soegijapranata Catholic University seeks to improve the ability of women in terms of environmental preservation by organizing socialization of women as agents of environmental care to the Women's Organizations Association in Semarang City. The socialization was conducted with a participatory approach in which the participants are active in training and then also active in the development of eco-print products and efforts to disseminate environmental awareness. These outreach activities produce positive results that women have great potential as agents of change in the environmental care movement. in terms of the socialization process, in order to run well, the women's groups must have the potential to disseminate the results of socialization. The criteria for the women's group is to be able to represent the original group so that it can become the next media for socialization and be active on social media that is popular in the community, namely Instagram. Furthermore, this activity also found that training media as a means of socialization must be interesting, that is, easily made (done) by the trainees, the results are good so it is interesting to be seen and imitated by other parties, easy for replication, even trainees can immediately become trainers for other party.